POSITIONING ANALYSES ON NEUROLOGY CLINIC SERVICES IN BETHESDA HOSPITAL, YOGYAKARTA - Rizal Sinulingga, Syamsul; Hendartini, Juliarti; Yulia A.W, Yulia A.W (Jurnal Kesehatan - STIKes Prima Nusantara, 2010)
Background: Business environment, now day, become more turbulent and competitive. The competition among hospital as social institution previously was considered as taboo, however, today it become important as maintaining the life of hospital organization. Given this situation, hospital should determine its positioning to make differentiation from competitor over product or services that being offered. Objective: This research intended to describe and determine neurology clinic services position of Bethesda hospital over Panti Rapih Hospital according to consumer perception. Method: This research is descriptive research with cross sectional survey design. Sample was taken used systematic sampling technique. Research subjects are 200 patient neurology clinics in each hospital. Method that being used is multidimensional scalling (MDS) Result: MDS analyzes reveals that position of each hospital attributes forming into group and several attribute were being closer and separated. Each hospital attributes have evenly distributes and located in competitive-local quadrant. Competition is not frontally colliding. Attributes point is being distribute, which mean that there are no closely competition except for human resource and philosophy that indicate closely competition. Each hospital seek to differentiate competitor’s attribute determines positioning. Conclusion: Competition does not frontally occur. Most attribute were having separated point, however, few were in close point that is human resources attribute and hospitals philosophy and policy that indicate tight competition.